Communities improve water management in Burkina Faso - Benson, Vivienne; Elias, Marlène; Traoré, Aurokiatou (Impact Initiative, 2019)
Globally, water scarcity and poor water quality have a major impact on food security and livelihoods. While there has been significant progress in the past decade, and over 90 per cent of the world’s population now has access to clean drinking water, there is still a long way to go to reach the most marginalised and ensure that water is protected from degradation. The set-up of ‘Innovation Platforms’ in Burkina Faso around two small water reservoirs meant that diverse members of rural communities, agricultural agents, and NGOs could reconcile differences and manage their most precious resource in harmony.